High RIG‐I expression in ovarian cancer associates with an immune‐escape signature and poor clinical outcome. Issue 7 (19th December 2019) - Wolf, Dominik; Fiegl, Heidi; Zeimet, Alain G.; Wieser, Verena; Marth, Christian; Sprung, Susanne; Sopper, Sieghart; Hartmann, Gunther; Reimer, Daniel; Boesch, Maximilian
Abstract : Ovarian cancer (OC) is the most lethal gynecological malignancy, with platinum‐based chemotherapy remaining the mainstay for adjuvant treatment after surgery. The lack of indication for immunotherapy may at least in part result from the lack of suitable biomarkers allowing stratification of potentially responding patients. In this monocentric study of 141 cases with OC, we used real‐time quantitative PCR to assess the expression of retinoic acid‐inducible gene‐I (RIG‐I) in primary tumor and healthy ovarian control tissues. RIG‐I expression was correlated to various clinicopathological characteristics as well as to a set of molecular and immunological markers. The prognostic significance of RIG‐I expression was queried in univariate and multivariate analyses and validated in an independent cohort. RIG‐I was overexpressed in the cancerous ovary and correlated with a higher tumor grade. The more aggressive Type‐II cancers and cancers with inactivating p53 mutations exhibited higher RIG‐I expression. RIG‐I levels were also elevated in cancers that recurred after remission or were platinum‐refractory. Survival analyses disclosed RIG‐I as an independent marker of poor outcome in OC. Continuative analyses revealed the molecular and immunological correlates of RIG‐I expression in the tumor microenvironment, including interferon production and a distinct immune‐regulatory signature involving checkpoint molecules (PD‐L1/PD‐1), the RNA‐editing enzyme ADAR1 and the regulatory T cell‐specific transcription factor FoxP3. We conclude that high RIG‐I expression associates with poor outcome in OC, which is explainable by local immunosuppression in the tumor bed. RIG‐I expression may inform checkpoint blockade and/or RIG‐I agonistic targeting in a subset of high‐risk OC patients. Abstract : What's new? Previous evidence suggests that the antiviral helicase RIG‐I bears tumor‐suppressive activity. The clinical significance of RIG‐I in gynecological cancer remains unclear, however. This single‐center, retrospective, explorative biomarker study of 141 cases with epithelial ovarian cancer (OC) reveals the negative prognostic impact of RIG‐I. RIG‐I is overexpressed in OC tissue, particularly in the more aggressive type‐II OCs, and is an independent prognostic marker for overall survival. RIG‐I high‐expressing tumors carry an interferon signature, linking RIG‐I activation to a cancer microenvironment fostering tumor immune‐evasion including upregulation of immune checkpoints. RIG‐I expression may indicate high‐risk OC patients who may benefit from immunotherapeutic intervention.